Nederlandse walvisvaarders op Nova Zembla: De beschrijving van N. Ozereckowsky uit de 18de eeuw - Maticsák, Sándor; Pusztai, Gábor (Acta Neerlandica, 2022)
The Russian Orenburg expedition made important discoveries in Russia’s inlands between 1768 and 1774. One of the members of the expedition Nikolai Ozereckowsky (1750–1827), who was only eighteen years old at the time, gave a description of Nova Zembla. In 1788, information of local fishermen was added by Ozereckowsky to this description, of which one was a short passage about Dutch sailors. In our article we would like to shed light on, besides the original text, the background of the Orenburg expedition and Dutch whaling.